Pengaruh Masa Kerja Petani Pengguna Pestisida Terhadap Kadar SGPT (Serum Glutamic Pyruvic Transaminase) - Muawanah Muawanah; Nur Qadri Rasyid; Rahmawati; Nurhikmah Nurhikmah (LPPM POLBITRADA, 2025)
To improve the quality and productivity of agricultural products, farmers use pesticides as chemicals that function to control the growth of pests, diseases, and weeds. Excessive use of pesticides can have health impacts, one of which is impaired liver function because pesticides will accumulate in the liver and cannot be broken down or excreted. This will trigger an increase in the number of free radicals and cause hepatocyte cell damage, as well as increase SGPT levels. SGPT is an enzyme normally found in liver cells, but when there is a disruption in liver cells, the enzyme is released into the bloodstream, causing levels to increase and become an indicator of liver dysfunction. This study aims to determine the effect of the work period of farmers using pesticides on SGPT (Serum Glutamic Pyruvate Transaminase) levels. The examination method used is the Photometric method with Bio System BA 200 with a number of 20 samples. Based on the results of the research, it was found that from 20 samples of farmers using pesticides, SGPT levels were still within normal limits according to the reference value of SGPT levels (Male=42 U/L, Female=32 U/L). The results of the SPSS 23 statistical test with a linear regression test obtained a significant value of p (0.237) > α > (0.05) in the work period, so there was no difference in SGPT levels. Thus, it can be concluded that there is no significant effect between the work period of farmers using pesticides with SGPT levels.